2017
DOI: 10.1093/bja/aew448
|View full text |Cite
|
Sign up to set email alerts
|

Influence of head and neck position on ventilation using the air-Q® SP airway in anaesthetized paralysed patients: a prospective randomized crossover study

Abstract: NCT02402387.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 21 publications
4
51
0
Order By: Relevance
“…Similar results have been reported in studies using different SGADs in both children and adults. [ 16 17 ] Flexion results in a decrease in the longitudinal tension on anterior pharyngeal muscles, which settle over the mask of SGADs providing better seal and reverse is seen during extension. In the current study, group B resulted in a 10.2% increase in mean OSP compared to 7% with I-gel™ from neutral to the flexed neck position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported in studies using different SGADs in both children and adults. [ 16 17 ] Flexion results in a decrease in the longitudinal tension on anterior pharyngeal muscles, which settle over the mask of SGADs providing better seal and reverse is seen during extension. In the current study, group B resulted in a 10.2% increase in mean OSP compared to 7% with I-gel™ from neutral to the flexed neck position.…”
Section: Discussionmentioning
confidence: 99%
“…But the area of cross-section of ventilation holes is larger in Baska mask ® (30 × 6 mm 2 for size 4) as compared to I-gel™ (16 × 7 mm 2 for size 4) hence providing an eminent buffer area leading to better preservation of ventilation and added advantage over I-gel™ during neck flexion to tide over limited laryngeal space [ Figure 3 ]. [ 17 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although the most convenient method to assess the accuracy of anatomic placement of the LMA for clinical studies is fiberoptic examination, the value of the fiberoptic scoring system as a means of assessing proper positioning and airway seal function of the LMA has been debatable [4, 11, 19, 20]. Some studies demonstrated that there was no correlation between position and tightness of the LMA, and no prediction of tightness was possible [7, 20].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure safety, the maximal allowable OPLP was fixed at 40 cmH 2 O. Because position of head can impact the OPLP [11], the head and neck were kept in the sniffing position during the study. A fiberoptic scope was passed through the LMA tube to a position 1 cm proximal to the end of the tube, and the fiberoptic position was evaluated using the fiberoptic scoring system [5, 14]: 4, only the vocal cords seen; 3, vocal cords plus posterior epiglottis seen; 2, vocal cords plus anterior epiglottis seen; 1, vocal cords not seen, but function adequate; and 0, functional failure with the vocal cords invisible.…”
Section: Methodsmentioning
confidence: 99%
“…[15] Compared with tracheal intubation, the use of SADs has been shown to reduce the incidence of postoperative pharyngolaryngeal complications and shorten recovery time from anesthesia. [4] Despite these advantages, the performance of SADs can be affected by head and neck position. [5,6]…”
Section: Introductionmentioning
confidence: 99%